Distribution. Circumpolar in the Southern Ocean. in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Circumpolar in the Southern Ocean. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 174, DOI: 10.5281/zenodo.6607185